EVALUASI KEBUTUHAN RUANG PARKIR DI KAMPUS UNIVERSITAS BRAWIJAYA - Wahyunita R, Nuzul; Sulistio, Harnen; Suharyanto, Agus (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2015)
Evaluasi Kebutuhan Ruang Parkir di Kampus Universitas BrawijayaEvaluation of Needs A Parking Space On The Campus Brawijaya UniversityNuzul Wahyunita R1, Harnen Sulistio2 , Agus Suharyanto31,2,3Jurusan Teknik Sipil, Fakultas TeknikUniversitas BrawijayaJln. MT. Haryono, Malang, Jatime-mail: nuzul_wr@yahoo.comAbstractAn increasing number of students, faculty and staff that occurred at UB will produce a number of traffic movements are quite large due to use of each vehicle to campus, so that the number of vehicles entering volume resulting difficulty in obtaining adequate parking. Therefore this study aims to find out what the existing parking capacity at UB Campus, knowing what the parking needs at the present time, how the model predictions parking needs for the purpose of parking for 5 years to come, and make recommendations to the parking arrangement of five years to come. Models obtained from multiple linear regression analysis are: Y1 = 132.437 + 0.068 X2 0,780 R2 value, and Y2 = 17.149 + 0249 X3 0,952 R2 value. The capacity of the existing car park at the Campus UB at this time in the amount of 624 SRP, while the capacity of the motorcycle that is equal to 5.312 SRP, and the need for car parking space at the moment at UB in the amount of 693 SRP, and to the needs of motorcycle parking space that is equal to 5.902 SRP. In order to meet the parking needs for the coming 5 years is the provision of alternative parking deck in 5 regions, with a total overall SRP for motorcycle with an area of 1.405 SRP of 2.107,5 m2 and parking for four-wheeled vehicles by 35 SRP with a land area of 437,5 m2 parkingKeywords : Parking capacity, SRP, Regression Analysis, Parking BuildingAbstrakPeningkatan jumlah mahasiswa, dosen dan karyawan yang terjadi di UB akan menghasilkan jumlah pergerakan lalu lintas yang besar karena menggunakan kendaraan pribadi menuju kampus, sehingga mengakibatkan kesulitan mendapatkan tempat parkir. Oleh karena itu penelitian ini bertujuan untuk mengetahui berapakah kapasitas parkir, berapakah kebutuhan parkir pada saat sekarang , bagaimanakah model kebutuhan parkir untuk keperluan prediksi parkir untuk 5 tahun yang akan datang, membuat rekomendasi penataan parkir pada 5 tahun yang akan datang. Model yang didapatkan dari analisa regresi linier berganda adalah :Y1 = 132,437 + 0.068 X2 memiliki nilai R2 0.780, dan Y2 = 17,149 + 0.249 X3 memiliki nilai R2 0.952. Kapasitas parkir mobil yaitu 624 SRP, sedangkan kapasitas sepeda motor yaitu 5.312 SRP. Kebutuhan ruang parkir mobil yaitu 693 SRP, dan kebutuhan ruang parkir sepeda motor yaitu 5.902 SRP. Guna memenuhi kebutuhan parkir untuk 5 tahun yang akan datang adalah dengan penyediaan alternatif gedung parkir di 5 kawasan, dengan total SRP keseluruhan untuk sepeda motor 1.405 SRP dengan luas parkir 2.107,5 m2 dan untuk mobil sebesar 35 SRP dengan luas parkir sebesar 437,5 m2Kata Kunci: Kapasitas Parkir, SRP, Analisa Regresi, Gedung Parkir